2022
DOI: 10.3389/fpsyt.2022.895224
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Depression and Anxiety Among Admitted People With Heart Disease Conditions: A Cross-Sectional Hospital-Based Study in a Bangladeshi Population During the COVID-19

Abstract: ObjectiveDepression and anxiety are widespread and chronic among patients with heart disease. We wanted to determine the proportion of heart patients with depression and anxiety levels as well as factors contributing toward depression and anxiety among hospitalized heart disease patients in Dhaka, Bangladesh during the COVID-19 era.MethodsThe study comprised a total of 384 participants with a confirmed heart disease diagnosis. We conducted a cross-sectional study from 5th March to 27th June 2021. The hospital-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…5 Amin et al in their respective study also found significant association between the use of smoking followed by alcohol for the development of cardiovascular diseases and psychiatric illness. 12 This finding was also evidenced by Jha et al in their respectful study. 4 This study found that smoking was prevalent in 76.25% of CVD patients, while alcohol abuse was identified in 73.75%.…”
Section: Resultssupporting
confidence: 69%
“…5 Amin et al in their respective study also found significant association between the use of smoking followed by alcohol for the development of cardiovascular diseases and psychiatric illness. 12 This finding was also evidenced by Jha et al in their respectful study. 4 This study found that smoking was prevalent in 76.25% of CVD patients, while alcohol abuse was identified in 73.75%.…”
Section: Resultssupporting
confidence: 69%
“…Our present study was conducted in the context of the post-pandemic ages of COVID-19, when urgent and large-scale infectious events have been well contained in China. In contrast, the impact of pandemic crisis and corresponding normalized prevention and control measures, such as social distancing and activity restriction created an unpleasant atmosphere of vigilance and alarm and caused uncertainty, social isolation and loneness, and financial loss, thereby potentially triggering a range of negative emotional responses in the general population and patients with COVID-19 and/or other chronic conditions, including anxiety and depression [ [41] , [42] , [43] ]. This might explained the significant but weak-to-moderate association between fear and anxiety/depression among community dwelling CS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Each question is scored on a scale from zero (indicating no impairment) to three (indicating severe impairment), resulting in a maximum score of 21 for both anxiety and depression [ 37 ]. The HADS has been widely used to assess anxiety and depression in cardiac patients, and a study by Amin et al (2022) [ 38 ] reported a Cronbach’s alpha value of 0.70, indicating good internal consistency. To aid in the interpretation of scores, a classification scheme can be applied: scores ranging from 0 to 7 suggest the absence of clinical symptoms, scores between 8 and 10 indicate moderate levels of depression or anxiety, and scores from 11 to 21 indicate the presence of clinically significant depression or anxiety.…”
Section: Methodology and Materialsmentioning
confidence: 99%